Temperature dependent EUV spectra of Gd, Tb and Dy ions observed in the Large Helical Device. (28th May 2015) - Suzuki, C; Koike, F; Murakami, I; Tamura, N; Sudo, S
Abstract: We have observed a number of different types of extreme ultraviolet (EUV) spectra from highly charged gadolinium (Gd), terbium (Tb) and dysprosium (Dy) ions in optically thin plasmas produced in the Large Helical Device at the National Institute for Fusion Science. Temporal changes in EUV spectra in the 6–9 nm region subsequent to the injections of solid pellets were measured by a grazing incidence spectrometer. The spectra rapidly change from discrete features into unresolved transition arrays (UTAs) following a drop in the electron temperature after the heating power is reduced. In particular, extremely narrowed UTA features, which comprise spectral lines of Ag-like, Pd-like and neighboring ion stages, are observed when the peak electron temperature is less than 0.45 keV due to the formation of hollow plasmas. Some discrete spectral lines of Cu-like and Ag-like ions have been identified in the high and low temperature plasmas, respectively, some of which are experimentally identified for the first time.